Trading airport time slots: Market design with complex constraints. (March 2021) - Bichler, Martin; Littmann, Richard; Waldherr, Stefan
Abstract : highlights: We propose a market design for the allocation of airport time slots. The market design considers financial constraints of airlines and core stability. In spite of significant computational hardness, we can solve relevant problem sizes. Abstract: Due to the lasting growth in air traffic, many international airports have reached their capacity limits. Access to major airports is granted through the assignment of airport time slots. Current practices of allocating these time slots via grandfathering are widely regarded as inefficient by experts. New market mechanisms need to take into account synergistic valuations of airlines for departure and arrival time slots, as well as financial constraints of the participating airlines for the many time slots available. Unfortunately, computing core-stable outcomes in such environments is Σ 2 p -hard. Such problems are typically considered intractable. We introduce bilevel integer optimization models for airport time slot trading and compute core-stable outcomes, i.e. allocations and prices such that no coalition can beneficially deviate. Interestingly, despite the computational hardness of the underlying problem numerical experiments show that instances of practically relevant size can be solved in due time. The proposed market design provides a solution that addresses the specific constraints of airport time slot markets, a precondition for adoption in the field.